Associations Among Trauma Exposure, Callous-Unemotionality, Race or Ethnicity, and Gang Involvement in Justice-Involved Youth - Mendez, Lucybel (Criminal justice and behavior, 2020)
The current study examined the association between trauma exposure and gang involvement and whether these interrelations were explained by callous-unemotionality (CU). In addition, the current study examined whether the associations among these variables differed based on race or ethnicity. A sample of 829 justice-involved youth (74% boys, 45% participants of color) recruited from a detention center completed self-report measures of trauma exposure, CU, and gang involvement. A moderated mediation analysis indicated that CU helped explain the association between trauma exposure and gang involvement for non-Hispanic White participants only. In contrast, the direct association between trauma exposure and gang involvement was significant across racial or ethnic groups. These findings highlight the importance of a trauma-informed perspective on intervening and preventing gang involvement among youth.